Manajemen Konflik Pembangunan Tower Telkomsel dengan Masyarakat di Kelurahan Talang Jambe Kota Palembang - Mariska, Revi; Minako, Muchlis (Indonesian Journal of Social Development, 2023)
Technological advances are currently growing rapidly, moreover the telecommunications sector is experiencing exponential growth. When they wanted to build a tower on one of the residents’ lands, there was a slight obstacle, namely the occurrence of conflict in the community. Conflict is an event or social phenomenon that is part of the dynamics of human life. Often conflicts have a negative impact on conflicting parties such as the emergence of ongoing hostilities, material losses and even fatalities. Even so, conflict can also be a supporting aspect in a better survival. This can happen if the conflict can be managed properly and is able to take advantage of the conditions or background of the conflict which can unite the conflicting parties. In this article, the author seeks to make an effort to solve problems in conflict management in the form of mediation of conflicts that occurred in Talang Jambe, Palembang City, which involved the community, RT, and Telkomsel.